Responses to increasing exercise upon reaching the anaerobic threshold, and their control by the central nervous system - Peinado, A. B.; Rojo, J. J.; Calderón, F. J.; Maffulli, N. (BMC Sports Science, Medicine and Rehabilitation, 2014)
The anaerobic threshold (AT) has been one of the most studied of all physiological variables. Many authors have proposed the use of several markers to determine the moment at with the AT is reached. The present work discusses the physiological responses made to exercise - the measurement of which indicates the point at which the AT is reached - and how these responses might be controlled by the central nervous system. The detection of the AT having been reached is a sign for the central nervous system (CNS) to respond via an increase in efferent activity via the peripheral nervous system (PNS). An increase in CNS and PNS activities are related to changes in ventilation, cardiovascular function, and gland and muscle function. The directing action of the central command (CC) allows for the coordination of the autonomous and motor systems, suggesting that the AT can be identified in the many ways: changes in lactate, ventilation, plasma catecholamines, heart rate (HR), salivary amylase and muscular electrical activity. This change in response could be indicative that the organism would face failure if the exercise load continued to increase. To avoid this, the CC manages the efferent signals that show the organism that it is running out of homeostatic potential.